“I’ll Show You!”: Reflections on Disabled Children’s Points of View and the Use of Action Cameras in Inclusive, Critical, Qualitative Research - Kassi A. Boyd; Jennifer Leo; Nancy L. I. Spencer; Shanon K. Phelan (International Journal of Qualitative Methods)
Disabled children are often excluded from research about their own lives due to researchers’ reliance on inaccessible methods and ableist assumptions about their capabilities. Inclusive research approaches that prioritize accessibility, meaningful engagement, dignity, and ethics create space for research with and by disabled children. Accessible methods for data generation play a central role in inclusive research. For example, action cameras have the potential to shine light on disabled children’s perspectives from both socio-spatial and socio-cultural standpoints, providing unique access to disabled children’s points of view. While the use of action cameras has become increasingly popular across the social sciences, there is a paucity of literature that discusses the use of action cameras in data generation with disabled children. The purpose of this paper is to discuss the possibilities and challenges of using action cameras as a tool for data generation with disabled children. Drawing on lessons learned during a research project about disabled children’s and their families’ experiences of inclusion at a playground labelled as “inclusive”, we reflect on the use of action cameras and situate our experiences within a broader dialogue about reflexive, methodological, and ethical considerations for conducting inclusive, critical, qualitative research with disabled children.